Upaya Meningkatkan Kemampuan Psikososial Anak Usia Dini Melalui Bermain Peran Makro - Fida Arinal Haqiyah; Restu Salma Sya'bani; Rina Listiawati; Hidayati; Anita Chandra Dewi Sagala (UNIB Press, 2026)
This study aimed to improve early childhood psychosocial abilities through macro role-playing activities at TPA Aisyiyah Purwodadi. The study employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages conducted in two cycles. The research subjects were 10 children aged 3 years. Data collection techniques included observation, documentation, and field notes. The results showed that children’s psychosocial abilities improved after the implementation of the macro role-playing method. In the pre-cycle stage, 60% of children were categorized as Not Yet Developed (NYD) and 40% as Beginning to Develop (BTD). In Cycle I, there was an improvement, with 50% of children reaching the Developing as Expected (DAE) category and 10% reaching the Very Well Developed (VWD) category. In Cycle II, the improvement became more significant, with 80% of children achieving the Very Well Developed (VWD) category. The findings indicate that macro role-playing is effective in improving children’s psychosocial abilities, including cooperation, self-confidence, emotional control, communication, and social interaction skill